ANALISIS YURIDIS PERMOHONAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG OLEH DEBITUR DI MASA PANDEMI COVID-19 - Miswar Miswar; Marzuki Marzuki; Nelvitia Purba (LPPM YPITI, 2021)
Based on the results of the research, postponement of the Payment Obligation according to POJK Number 11 / POJK.03 /2020, the debtor can apply for credit relaxation directly to the bank concerned by meeting the predetermined requirements. If the debtor uses the provisions of the K-PKPU Law, the debtor submits a PKPU application to the court, either after the bankruptcy application or prior to the creditor's application for bankruptcy. Submitting a request for a postponement of Debt Payment obligations in accordance with the provisions of POJK Number 11/ POJK.03 / 2020, the main requirement that must be fulfilled by the debtor is that the debtor is the party affected by the Covid-19 pandemic, which can be assessed from the debtor himself, namely being exposed to positive covid -19 or based on an assessment of the business sector carried out by a debtor who has been determined to be a business sector affected by Covid-19. Postponement of Debt Payment Obligations by Debtors during the Covid-19 epidemic in POJK Number 11/POJK.03 / 2020, causing multiple interpretations in its implementation.